Reasoning and planning of therapeutic occupation activities - Melo-Dias,Carlos (2016)
BACKGROUND: Psychosocial rehabilitation offers the patient the opportunity to reach the maximum functioning potential in community while performing physical, emotional and intellectual skills. Therapeutic Occupation Activities are systematic activities which structure and guide the participant's functional performance, within the interpersonal nurse-client relationship, and empowering for autonomy and promoting satisfaction and accomplishment in both occupation and recreation. AIM: To explore the reasoning and planning that substantiates the Therapeutic Occupation Activities (TOA’s) in Mental Health and Psychiatric Nursing. METHODS: Using a concept-based design, the methodological step-by-step framework to build the reasoning will be described as well as the planning which substantiates the Targeted Nursing Interventions (TNI) on TOA’s will be described. CONCLUSION: The clinical reasoning in Nursing allows for an updated, adaptive, sensitive and constructive decision-making. The various domains in which the TOA’s are developed reveal the holistic nature of the intervention and the impact of Nursing in the individuals’ life and health. The preservation of the optimal well-being and the prevention of relapses and long hospital stays are ultimate therapeutic indications which expand the philosophies of care and lead to achievable benefits, such as the feeling of social utility and the building up of self-esteem and self-image of those involved. The implications for the clinical practice derive from the association between social functioning and personal satisfaction, positive and corrective reinforcement in performance, and from consistency and proportionality of modelling, assertiveness and generalization. The use of clinical indicators consistent with and sensitive to the Nurse's intervention has a clinical influence on the participants’ performance and outcomes.